2019
DOI: 10.3390/electronics8101109
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Genetically Identical Left and Right Irises Using a Convolutional Neural Network

Abstract: As one of the most reliable biometric identification techniques, iris recognition has focused on the differences in iris textures without considering the similarities. In this work, we investigate the correlation between the left and right irises of an individual using a VGG16 convolutional neural network. Experimental results with two independent iris datasets show that a remarkably high classification accuracy of larger than 94% can be achieved when identifying if two irises (left and right) are from the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Deep learning is utilized for classifying several types of medical images and showed great performance [10,46,47]. However, some limitations are frequently encountered when utilizing deep learning.…”
Section: Lack Of Training Data Issuementioning
confidence: 99%
“…Deep learning is utilized for classifying several types of medical images and showed great performance [10,46,47]. However, some limitations are frequently encountered when utilizing deep learning.…”
Section: Lack Of Training Data Issuementioning
confidence: 99%
“…The results showed that the Multimodal Biometric System's feature level fusion improved gender classification performance significantly. Additionally, Fang et al (2019) , employed a convolutional neural network to classify genetically identical left and right irises; however, the iris identification process focused only on the differences in iris textures, neglecting similarities. They used a VGG16 convolutional neural network to study the link between an individual's left and right irises.…”
Section: Literatures Reviewmentioning
confidence: 99%
“…CNNs employ very less pre-processing compared to other image classification techniques. This implies that the network learns to optimize the filters (or kernels) by automatic learning, while in conventional methods these filters are hand-engineered (Fang et al, 2019).…”
Section: Deep Learning By Convolutional Neural Networkmentioning
confidence: 99%
“…This CNN has been employed to solve several computer vision tasks [19,20]. It has shown great performance in different medical applications [21,22].…”
Section: Deep Learning (Dl)mentioning
confidence: 99%